Molecular Mechanisms of Multi-Organ Failure in COVID-19 and Potential of Stem Cell Therapy - Aditya Bhalerao; Snehal Raut; Behnam Noorani; Salvatore Mancuso; Luca Cucullo (Cells, 2021)
As the number of confirmed cases and deaths occurring from Coronavirus disease 2019 (COVID-19) surges worldwide, health experts are striving hard to fully comprehend the extent of damage caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Although COVID-19 primarily manifests itself in the form of severe respiratory distress, it is also known to cause systemic damage to almost all major organs and organ systems within the body. In this review, we discuss the molecular mechanisms leading to multi-organ failure seen in COVID-19 patients. We also examine the potential of stem cell therapy in treating COVID-19 multi-organ failure cases.